Indoor tracking system using wireless fidelity - Ebora, Rose Ann L. (Animo Repository, 2010)
Research about location and tracking system is divided into two, outdoor and indoor settings. In outdoor setting, Global Positioning System is widely used. But it does not function properly in indoor areas due to the obstacles blocking the view of satellites. In response to its limitation, systems for indoor settings are being developed using Wireless Local Area Network. However, the results obtained are still inaccurate. Further studies are done in order to improve the results. Some factors that affect the performance of the system include access points and obstacles, such as walls and furniture. The number and the position of access points vary with respect to the area where the system is being deployed. Inaccurate number and positioning of access points have effects on the result. Existing wireless tracking systems consider the geographic information of the environment such as the presence of obstacles, in location estimation. However, the obstacles are being treated uniformly. Different types of obstacles have their own signal attenuation factor. This study shows that there is improvement in the performance of a location and tracking system by considering the number of access points used and their position by 1.29%, and the signal attenuation factor of the obstacles present in environment of the system by 0.99%. Treating the signal attenuation factor of the obstacles also produces better results rather than treating the obstacles with a fix value. The improvement in the results is slight changes since its significance is dependent to the floor plan, especially with a larger the place is with different sizes of rooms, where the system is to be deployed.